Hadits-Hadits Tentang Pendidikan : (Suatu Telaah Tentang Pentingnya Pendidikan Anak) - Amanda Amanda; Alhamida Alhamida; Elvita Sarah; Layli Sartika; Nurul Aini; Wismanto Wismanto (Pusat Riset dan Inovasi Nasional, 2024)
Is very important in shaping the nature and character of man to be perfect man is education. Through education, be it family, school, or neighborhood, people can open mind for instance that there is nothing in the universe, there are a lot of science. From the start that there is in humanity itself up space that is difficult to reach by the senses and in the end thinking that the universe is the creator and owner.amongthe rule was one of a child's education should be noted that education in childhood that will affect the character of the child as an adult later. Education of children is not only done when they are still small. But, carried in the womb until he grew up. Hadith as part of the essential teachings of islam have so many precious cargo that can be used as a foothold in the education of children of this discourse. Therefore, the authors will describe some of the hadith related to the education of children.The purpose of this study was to examine and analyze verses relating to the concept of child education in the Qur'an and its implementation in the family. The research method used in this research is qualitative research through literature review using a maudhui interpretation approach. This study concludes that there are six terms for children in the Qur'an, including ghulam, walad, dzurriyah, ibn, tifl, and shabiy, each of which has a correlation with the concept of children's education. The concept of child education states that in educating children, parents are the first milestone in educating children, in this case the family plays an important role in the education process. In addition, in the concept of educating children there are also methods that must be considered. Among these methods are: 1) the exemplary method, 2) Habituation Method, 3) The method of advice, and 4) monitoring methods. This study recommends that more in-depth research and analysis be carried out with more applicable theories